Pembelajaran Integratif: Menyimak Puisi dan Menulis Cerita Pendek - Dewi Syafrina (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2021)
Language skills are commonly integrated in Indonesian language learning. In this integration, student activities involving listening and reading skills will lead to speaking and writing activities. However, in the learning process, the integration is always related to the same type of text. In fact, teachers can combine different types in learning Indonesian. Therefore, the aim of this article is to explain the integration of listening poetry and writing short stories. The integration will be explained in the discussion section in which the relationship between listening poetry and writing short stories and the implementation in Indonesian language learning are discussed. This article is expected to be used as a reference in Indonesian language learning so that there is an involvement of various texts in writing short stories.